Heartworm Disease (Dirofilaria immitis) in Two Roaming Dogs From the Urban Area of Castel Volturno, Southern Italy - Santoro, Mario; Miletti, Gianluca; Vangone, Lucia; Spadari, Luisa; Reccia, Stefano; Fusco, Giovanna (Frontiers in Veterinary Science, 2019)
The zoonotic filarioid nematode Dirofilaria immitis is transmitted by bloodsucking mosquitoes and causes heartworm disease in dogs and wild canines. In the last decade D. immitis has spread in southern Europe including Italy. Few autochthonous foci of infection have been reported in previously non-endemic areas of southern Italy based only on the identification of microfilariae, antigen and serological tests and polymerase chain reaction assay from both the blood of dogs and mosquito vectors with no description of cases of heartworm disease in both domestic and wild canines. Here we report for first on two cases of heartworm disease found at post-mortem examination in two roaming dogs from the urban area of Castel Volturno in Campania region of southern Italy. Immunological analyses of 11 roaming dogs from the same pack of those two submitted for necropsy, and available necropsy data from the dogs recovered from the Campania region along the past 10 years were both negative for D. immitis infection. Although rare in southern Italy, these two cases are noteworthy because D. immitis may cause serious human infection. We highlight the need to identify the mosquito vectors of heartworm disease in this area using sensitive molecular assay for D. immitis DNA for predicting and controlling the spread of infection. We strongly recommend the control and systematic treatment of the domestic and roaming dogs that could constitute the most important infection reservoir.